2018
DOI: 10.7554/elife.32303
|View full text |Cite
|
Sign up to set email alerts
|

Extreme heterogeneity of influenza virus infection in single cells

Abstract: Viral infection can dramatically alter a cell’s transcriptome. However, these changes have mostly been studied by bulk measurements on many cells. Here we use single-cell mRNA sequencing to examine the transcriptional consequences of influenza virus infection. We find extremely wide cell-to-cell variation in the productivity of viral transcription – viral transcripts comprise less than a percent of total mRNA in many infected cells, but a few cells derive over half their mRNA from virus. Some infected cells fa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
236
9

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 232 publications
(286 citation statements)
references
References 106 publications
(150 reference statements)
41
236
9
Order By: Relevance
“…We found that epithelial cells manifest a wide range of viralload states spanning two orders of magnitude, with 33%, 23%, and 44% of infected epithelial cells characterized respectively by low, medium, and high viral-load states (Figures 2D and S4C). Our data therefore confirm the previously reported epithelial heterogeneity in vitro (Russell et al, 2018) and, in addition, extends this result to include the case of in vivo infection. Interestingly, we found a clear distinction between epithelial cells and the rest of the cell types, with the observation that infected cells, in all of the non-epithelial cell types, mainly displayed low heterogeneity of viral-load states: the vast majority (85%-100% of the infected cells in the different cell types) maintained low viral-load states, whereas high viral-load states were maintained by only up to 1.1% of those cells ( Figure 2D and Table S3).…”
Section: Infected Epithelial Cells But Not Other Cell Types Show Asupporting
confidence: 92%
See 4 more Smart Citations
“…We found that epithelial cells manifest a wide range of viralload states spanning two orders of magnitude, with 33%, 23%, and 44% of infected epithelial cells characterized respectively by low, medium, and high viral-load states (Figures 2D and S4C). Our data therefore confirm the previously reported epithelial heterogeneity in vitro (Russell et al, 2018) and, in addition, extends this result to include the case of in vivo infection. Interestingly, we found a clear distinction between epithelial cells and the rest of the cell types, with the observation that infected cells, in all of the non-epithelial cell types, mainly displayed low heterogeneity of viral-load states: the vast majority (85%-100% of the infected cells in the different cell types) maintained low viral-load states, whereas high viral-load states were maintained by only up to 1.1% of those cells ( Figure 2D and Table S3).…”
Section: Infected Epithelial Cells But Not Other Cell Types Show Asupporting
confidence: 92%
“…Recent studies have demonstrated a wide range of intracellular virus-related states, including heterogeneity in viral transcription and virus titers. For example, in vitro infection of epithelial cells results in wide heterogeneity of transcriptional viral loads (Russell et al, 2018), and during in vitro infection, low viral loads are prevalent in Madin-Darby canine kidney epithelial (MDCK) cells (Brooke et al, 2013). Here, focusing on in vivo infection, we found that epithelial cells indeed display high viral-load heterogeneity, whereas the remaining cell types maintain low viral-load states ( Figure 2D).…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations